2020
DOI: 10.1002/cbin.11323
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐93‐5p expression in tumor tissue and its tumor suppressor function via targeting programmed death ligand‐1 in colorectal cancer

Abstract: This work aimed to investigate miR-93-5p expression in tumor tissue and its in vitro effects in colorectal cancer (CRC) by targeting programmed death ligand-1 (PD-L1). MiR-93-5p and PD-L1 expression was detected in CRC and adjacent normal tissues by quantitative real-time polymerase chain reaction and immunohistochemistry. The correlation between miR-93-5p and PD-L1 was validated by a dual-luciferase reporter assay. HCT116 and SW480 cells were divided into blank, miR-NC, miR-93-5p mimics, miR-93-5p inhibitor, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(22 citation statements)
references
References 47 publications
1
21
0
Order By: Relevance
“…These studies fully confirm that miRNA functions in CRC growth diversely, both as a carcinogenic and anticancer molecule. In previous studies, miR-93-5p showed a bidirectional effect in CRC progression, either by inhibiting PD-L1 from weakening CRC cell transfer (11) or by inhibiting cyclin-dependent kinase inhibitor 1A from enhancing the multidrug resistance of CRC cells (26). In the present study, we proved that miR-93-5p is a competitive miRNA of CTBP1-AS2 and is limited by the upregulated CTBP1-AS2.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…These studies fully confirm that miRNA functions in CRC growth diversely, both as a carcinogenic and anticancer molecule. In previous studies, miR-93-5p showed a bidirectional effect in CRC progression, either by inhibiting PD-L1 from weakening CRC cell transfer (11) or by inhibiting cyclin-dependent kinase inhibitor 1A from enhancing the multidrug resistance of CRC cells (26). In the present study, we proved that miR-93-5p is a competitive miRNA of CTBP1-AS2 and is limited by the upregulated CTBP1-AS2.…”
Section: Discussionsupporting
confidence: 66%
“…Various studies have discovered that miRNAs regulate tumor growth (9). As a miRNA, miR-93-5p inhibits the Hippo signaling pathway, thus promoting gastric cancer cell process (10), and its knockdown inhibits CRC cell proliferation and metastasis by targeting programmed death ligand 1 (PD-L1) (11). Functionally, miRNAs are competitively inhibited by lncRNAs, on the other hand, it binds to the 3 ′ untranslated region (3 ′ -UTR) of mRNAs.…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, epigenetic control of PD-L1 via DNA methyltransferase 1 notably influenced the response to chemotherapy (Huang et al, 2020). PD-L1 expression in CRC tissues was remarkably enhanced versus tumor-adjacent normal tissues, displaying a tight correlation to the differentiation and lymphatic metastasis of CRC patients (Chen et al, 2020). More significantly, the induction of immune checkpoints by malignancies can produce an immunosuppressive microenvironment, among which PD-L1 represents itself as the most frequently studied checkpoint (Payandeh et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we found that miR-93-5p could bind to HAGLR and that SRSF1 was targeted by miR-93-5p in TNBC cells. Though miR-93-5p appears to play different roles—either oncogenic or tumor-suppressive—in different cancer types [ 15 29 ], its tumor-restraining function in breast cancers, including TNBC, has already been revealed [ 16 17 ]. In addition, consistent with the findings of previous studies [ 30 ], SRSF1 was upregulated in TNBC cells and exerted a tumor-promoting function in TNBC.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, miR-93-5p was selected as a HAGLR-interacting miRNA. miR-93-5p may play tumor-suppressing roles in colorectal cancer [ 15 ] and may be an effective tumor inhibitor in breast cancers [ 16 ], including TNBC [ 17 ]. However, the interplay between HAGLR and miR-93-5p has not yet, to our knowledge, been explored in cancer cells, let alone the influence of their interaction on TNBC progression.…”
Section: Introductionmentioning
confidence: 99%